The Influence of Audit Independence, Experience and Accountability on Audit Quality Medan Public Accountant Office - Piter, Jhon; Sitompul, Melva Melany; Sisilia, Mariska (Elektriese: Jurnal Sains dan Teknologi Elektro, 2024)
The object of the research is a public accounting company in the city of Medan. The selection of these objects is due to the higher quality of the audit. Audit quality is the result of the job's performance in producing a quality audit. The variables of the study are independence, auditor experience, and accountability. Independence is a mental attitude that is free from the influence of others and is not dependent on others. Experience is a learning process and increases the development potential of formal and informal education. Responsibility is a form of obligation to manage the authority entrusted to him to achieve the goals that have been set. The research population is 40 managers, senior auditors, and junior auditors in the Medan public accountant office, and the sample is 30 auditors. Primary data was collected using a questionnaire. Research data was analyzed using multiple linear regression analysis, simultaneous determination of coefficients (F-Test), and partial (T-Test). Sampling is done using the non-probability sampling method. The results of the hypothesis test in this study show that independence has a significant impact on audit quality, auditor experience has a significant effect on audit quality, and accountability has a substantial impact on audit quality. Based on the results of this study, independence, auditor experience, and accountability simultaneously have a significant impact on audit quality.